If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying n + 36 = 40 Reorder the terms: 36 + n = 40 Solving 36 + n = 40 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + n = 40 + -36 Combine like terms: 36 + -36 = 0 0 + n = 40 + -36 n = 40 + -36 Combine like terms: 40 + -36 = 4 n = 4 Simplifying n = 4
| 3=n+1.5 | | 8x+14=-12 | | -9=g-2 | | f(x)=9x^2+2x+4 | | -8w-20=3w-13 | | 6n-7+3n+11=-23 | | 38+n=95 | | 41=30+n | | 2/3(6x+3)=4x+12 | | 7=n-33 | | -7/9m=14 | | 110/18 | | 0.123x-0.024=7.263 | | 14-w=1/5 | | 11.17=2.49+1.24n | | 2(2a+0.5)=3(a-0.6) | | 10t+-3=1t+15 | | 2E/(E-1)=2+5/2E | | 3/4x=4 | | 7z+-4=12+3z | | 24=4/5y | | 1.61+n=19.95 | | 5-2x(x+6)=14 | | 18a^5b^3/18a^5b^3 | | 15miles=ft | | 4y=2y+-10 | | 9x+6/18=20x+4/3x | | -1+(-5x+2)=-5x | | -8(4b+3)+(33b-8)=0 | | 19=5(x-2)-(x-9) | | 3(1)=-y+3 | | x(9x+12)=4x^2-22x+48 |